Cerebral microbleeds and intravenous thrombolysis: case report Micro-hemorragias cerebrais e trombólise endovenosa: relato de caso - Adriana Bastos Conforto; Leandro Tavares Lucato; Claudia da Costa Leite; Eli Faria Evaristo; Fábio Iuji Yamamoto; Milberto Scaff (Arquivos de Neuro-Psiquiatria)
Intravenous thrombolysis is an important procedure that has significant impact on ischemic stroke prognosis. However, intracranial hemorrhage (ICH) is a feared complication of this procedure. It has been suggested that cerebral microbleeds (CMBs) may increase the risk of ICH after thrombolysis. We report on a 69 years-old woman with multiple CMBs submitted to intravenous thrombolysis without complications. A trombólise endovenosa é um procedimento importante que tem impacto significativo sobre o prognóstico de pacientes com acidente vascular cerebral isquêmico. Contudo, a hemorragia intracraniana (HIC) é complicação temida deste procedimento. Foi sugerido que micro-hemorragias cerebrais (MHC) aumentem o risco de HIC após trombólise. Relatamos o caso de mulher de 69 anos com múltiplas MHCs submetida a trombólise endovenosa sem complicações.